Adverse Childhood Experiences of Violent Female Offenders: A Comparison of Homicide and Sexual Perpetrators. (June 2018) - Pflugradt, Dawn M.; Allen, Bradley P.; Zintsmaster, Amanda J.
Adverse childhood experiences are associated with a multitude of health and social problems. In addition to an increased risk of poor health, mental disorders, and substance abuse, childhood maltreatment is also significantly related to adult violent offending. Although gender-specific analyses suggest that early childhood maltreatment precedes later violence for males across offense categories, it is unknown whether this association also applies to different types of female offenders. This study explores the types and quantity of adverse childhood experiences for two groups of violent female offenders: perpetrators of intentional homicide ( N = 28) and perpetrators of sexual offenses ( N = 47). A nonparametric analysis using odds ratios (OR) indicated that female homicide perpetrators experienced significantly more adverse childhood experiences (as measured by the Adverse Childhood Experiences Questionnaire) than female sex offenders. Implications for future research are discussed.